Development of a Screening Tool for Pediatric Neuropathic Pain and Complex Regional Pain Syndrome: Pediatric PainSCAN. Issue 1 (January 2022) - Mesaroli, Giulia; Campbell, Fiona; Hundert, Amos; Birnie, Kathryn A.; Sun, Naiyi; Davidge, Kristen M.; Lalloo, Chitra; Davies-Chalmers, Cleo; Harris, Lauren; Stinson, Jennifer
Abstract : Objective: Neuropathic pain (NP) and complex regional pain syndrome (CRPS) in children can result in significant disability and emotional distress. Early assessment and treatment could potentially improve pain, function, quality of life, and reduce costs to the health care system. Currently, there are no screening tools for pediatric NP and CRPS. This research aimed to develop and establish the content validity of a screening tool for pediatric NP and CRPS using a phased approach. Materials and Methods: Phase I surveyed clinical experts using a modified Delphi procedure to elicit disease concepts for inclusion. In phase II, a consensus conference including clinicians, researchers, and people with lived experience, informed the initial item pool. Consensus for item inclusion was achieved using a nominal group technique for voting. Phase III used iterative rounds of cognitive interviews with children aged 8 to 18 years with CRPS or NP to evaluate the tool's comprehensiveness and individual item relevance and comprehensibility. Descriptive statistics were used to describe participant characteristics. Content analysis was used to analyze patient interviews. Results: Phase I (n=50) generated an initial item pool (22 items). Phase II generated a comprehensive item pool (50 items), after which an initial version of the screening tool was drafted. Following phase III (n=26) after item revision and elimination, 37 items remained. Discussion: The Pediatric PainSCAN is a novel screening tool that has undergone rigorous development and content validity testing. Further research is needed to conduct item reduction, determine scoring, and test additional measurement properties.